Desorption of copper ions from the polyamine-functionalized adsorbents: Behaviors and mechanisms - Changkun Liu; Xiaoyan Liang; Ji’an Liu; Wenxiang Yuan (Adsorption Science & Technology)
This paper is aiming at analyzing the desorption performance of the four polyamine-functionalized adsorbents after copper ion adsorption, with nitric acid as the desorption agent. The four adsorbents (namely, P-EDA, P-DETA, P-TETA and P-TEPA) studied were immobilized with ethylenediamine (EDA), diethylenetriamine (DETA), triethylenetetramine (TETA) and tetraethylenepentamine (TEPA), respectively. Nitric acid concentration, ionic strength, and solid-to-liquid (S/L) ratio were taken into consideration as the influencing factors on the desorption performance. The findings showed that higher desorption efficiency had no necessary connection with the higher concentration of nitric acid, and the highest desorption efficiency was realized for P-EDA and P-DETA at 0.10 mmol/L, and for P-TETA and P-TEPA at 0.25 mmol/L, in the nitric acid concentration range of 0.01–2.00 mmol/L studied. In addition, Ionic strength showed obvious influence on the desorption efficiency, and higher ionic strength resulted in significant lower desorption efficiency. Different S/L ratios studied showed almost no differences on the desorption efficiency. The copper ion desorption kinetics, best described by the Elovich model, was discovered to be very fast that more than 85% of the desorption efficiency was attained within 2 min. A slight decrease in Cu ion adsorption capacity was found through ten cycles of adsorption-desorption-regeneration for all the four adsorbents.